MULTI-AGENT SYSTEMS FOR INFORMATION MONITORING AND REAL-TIME CONTROL: MULTI-AGENT SYSTEMS FOR INFORMATION MONITORING AND REAL-TIME CONTROL - Eshankulov, Xamza (Центр Научных Публикаций (buxdu.uz), 2021)
АННОТАЦИЯ В этой статье мы представляем модель использования интеллектуальных агентов, чтобы помочь операторам достаточно быстро распознать потенциальную проблему и помочь предотвратить широкий спектр реальных сбоев. В этом документе также обсуждаются брокер знаний и динамическая база данных знаний. Термин «Брокер знаний» - это особый вид интеллектуального компьютерного брокера, который занимается знаниями посредством хранения, запроса, распространения или передачи их в качестве основной или второстепенной функции. ABSTRACT In this article, we present a model for using intelligent agents to help operators quickly recognize a potential problem and help prevent a wide range of real-world failures. This document also discusses knowledge broker and dynamic knowledge database. The term “knowledge broker” is a special kind of intelligent computer broker that deals with knowledge by storing, requesting, distributing or transmitting it as a primary or secondary function.